PEMISAHAN KEWENANGAN BANK INDONESIA DENGAN OTORITAS JASA KEUANGAN DALAM PENGAWASAN BANK - Ahmad Solahudin (Jurnal IUS Kajian Hukum dan Keadilan, 2015)
The development of the banking industry can not be separated from the Central Bank of Indonesia as an authority to supervise banks in Indonesia. Law number 23 year 1999 about the central bank of Indonesia is a reference to the regulations of central bank in carrying out their duties. In the 34 sections of Law number 23 year 1999 as amended by Law number 3 year 2004 mandated the transfer of authority to the supervision of central bank to new institutions, namely the Financial Services Authority. But in the 4 sections (1) subsections was declared the authority of Bank Indonesia, the central bank one of which is to regulate and supervise banks. So there is a conflict between the norms of the sections. So there is a conflict between the norm of the sections. There is also the contradiction of sections in the law number 21 in 2011 about financial services authority which led to a norm that is blurred namely between sections  40 to sections 7 of the letters d and sections 39 with sections 8 of the letters d related to the authority which has moved to the financial services authority but bank indonesia can still carry it out.Keywords: supervision, Indonesia Bank, Financial Services Authority